Imiquimod Boosts Interferon Response, and Decreases ACE2 and Pro-Inflammatory Response of Human Bronchial Epithelium in Asthma - Nieto-Fontarigo, Juan José; Tillgren, Sofia; Cerps, Samuel; Sverrild, Asger; Hvidtfeldt, Morten; Ramu, Sangeetha; Menzel, Mandy; Sander, Adam Frederik; Porsbjerg, Celeste; Uller, Lena (Frontiers in Immunology, 2021)
Background Both anti-viral and anti-inflammatory bronchial effects are warranted to treat viral infections in asthma. We sought to investigate if imiquimod, a TLR7 agonist, exhibits such dual actions in ex vivo cultured human bronchial epithelial cells (HBECs), targets for SARS-CoV-2 infectivity. Objective To investigate bronchial epithelial effects of imiquimod of potential importance for anti-viral treatment in asthmatic patients. Methods Effects of imiquimod alone were examined in HBECs from healthy (N=4) and asthmatic (N=18) donors. Mimicking SARS-CoV-2 infection, HBECs were stimulated with poly(I:C), a dsRNA analogue, or SARS-CoV-2 spike-protein 1 (SP1; receptor binding) with and without imiquimod treatment. Expression of SARS-CoV-2 receptor (ACE2), pro-inflammatory and anti-viral cytokines were analyzed by RT-qPCR, multiplex ELISA, western blot, and Nanostring and proteomic analyses. Results Imiquimod reduced ACE2 expression at baseline and after poly(I:C) stimulation. Imiquimod also reduced poly(I:C)-induced pro-inflammatory cytokines including IL-1β, IL-6, IL-8, and IL-33. Furthermore, imiquimod increased IFN-β expression, an effect potentiated in presence of poly(I:C) or SP1. Multiplex mRNA analysis verified enrichment in type-I IFN signaling concomitant with suppression of cytokine signaling pathways induced by imiquimod in presence of poly(I:C). Exploratory proteomic analyses revealed potentially protective effects of imiquimod on infections. Conclusion Imiquimod triggers viral resistance mechanisms in HBECs by decreasing ACE2 and increasing IFN-β expression. Additionally, imiquimod improves viral infection tolerance by reducing viral stimulus-induced epithelial cytokines involved in severe COVID-19 infection. Our imiquimod data highlight feasibility of producing pluripotent drugs potentially suited for anti-viral treatment in asthmatic subjects.